STUDENTS INDEPENDENT WORK AS A MAJOR FORM IN TEACHING PROCESS - Khodjaniyazova, U. (ILIM hám JÁMIYET, 2018)
The article deals with new educational paradigm where the student from passive user of knowledge turns into active subject who can formulate the problems, analyze them and find optimal solution and prove his correctness. Teacher’s role in organizing, conducting and assessing the students’ independent works is also analyzed.